Analisis Pengaruh Pelayanan Fiskus, Sanksi Perpajakan, dan Penerapan E-filling Terhadap Kepatuhan Wajib Pajak di KPP Pratama Surakarta - Destria Ayunda Rifana; Indra Lila Kusuma; Muhammad Tho’in; Erna Setyawati (Jurnal Akuntansi dan Pajak, 2021)
This study aims to determine and analyze the effect of taxation services, tax sanctions, and the application of e-filling on taxpayer compliance at the Surakarta Pratama Tax Service Office. The sampling technique is accidental sampling with the determination of respondents using the Slovin formula, the number of respondents is 100. Data obtained from the results of the questionnaire. The data analysis technique used is multiple linear regression and hypothesis testing using t test and F test with a significance level of 5%. So the results of the partial test (t test) and simultaneous test results (F test) indicate that the tax service, tax sanctions, and the application of e-filling have a significant effect on taxpayer compliance at KPP Pratama Surakarta. Keywords: taxation services, tax sanctions, application of e-filling and taxpayer compliance